2022
DOI: 10.1111/all.15318
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severe reactions in food allergy: Rapid evidence review with meta‐analysis

Abstract: This rapid review summarizes the most up to date evidence about the risk factors for severe food-induced allergic reactions. We searched three bibliographic databases for studies published between January 2010 and August 2021. We included 88 studies and synthesized the evidence narratively, undertaking meta-analysis where appropriate. Significant uncertainties remain with respect to the prediction of severe reactions, both anaphylaxis and/or severe anaphylaxis refractory to treatment. Prior anaphylaxis, an ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 157 publications
4
73
2
1
Order By: Relevance
“…Evaluating the results of our study, even among this Ara h 2 sensitized cohort, we did not find a connection between well-controlled asthma and reaction severity during peanut OFC or even the outcome in terms of positive and negative. Our results are in line with a recent review that found no evidence for asthma being a risk factor for severe reactions if asthma control was satisfactory [32]. Our findings are also supported by previous reports from Petterson et al and van Erp et al, who reported that asthma in general was not related to reaction severity in OFCs [11,31].…”
Section: Asthma and Severity Of Allergic Reactionssupporting
confidence: 93%
“…Evaluating the results of our study, even among this Ara h 2 sensitized cohort, we did not find a connection between well-controlled asthma and reaction severity during peanut OFC or even the outcome in terms of positive and negative. Our results are in line with a recent review that found no evidence for asthma being a risk factor for severe reactions if asthma control was satisfactory [32]. Our findings are also supported by previous reports from Petterson et al and van Erp et al, who reported that asthma in general was not related to reaction severity in OFCs [11,31].…”
Section: Asthma and Severity Of Allergic Reactionssupporting
confidence: 93%
“…3 Additionally,youngadults, especiallyinthesecondandthirddecadesoflife,areatincreased riskforfatalanaphylaxisduetofood. 8 Someofthisriskmaybebehaviouralandsomemaybephysiologic. 8 Forthesereasons,adults mayespeciallybenefitfromfoodallergytreatmentwithOIT,even iftheadverseeventsandtreatmentfailureratemaybehigher.On ©2022EAACIandJohnWileyandSonsA/S.PublishedbyJohnWileyandSonsLtd.…”
Section: Therateoffulldesensitizationwassignificantlylowerinadultsmentioning
confidence: 99%
“…In 2022, a metanalysis has assessed the risk factors for severe and/refractory to treatment anaphylactic reactions in FA 124 . Specifically, authors showed that prior anaphylaxis, 125 an asthma diagnosis, 126 IgE sensitization profile or basophil activation tests 127 are not good predictors.…”
Section: Management Optionsmentioning
confidence: 99%
“…119 In 2022, a metanalysis has assessed the risk factors for severe and/refractory to treatment anaphylactic reactions in FA. 124 Specifically, authors showed that prior anaphylaxis, 125 an asthma diagnosis, 126 IgE sensitization profile or basophil activation tests 127 are not good predictors. However, some IgE components may be suggestive of a higher risk of severe reaction, for example Pru p 3 for peach, 128 and the 2S albumins in tree nut allergy, 129,130 although this may be region-dependent.…”
Section: Severity Assessmentmentioning
confidence: 99%